Electrosynthesis of hierarchical Cu2O–Cu(OH)2 nanodendrites supported on carbon nanofibers/poly(para-phenylenediamine) nanocomposite as high-efficiency catalysts for methanol electrooxidation. (3rd June 2021) - Halim, El Mahdi; Perrot, Hubert; Sel, Ozlem; Debiemme-Chouvy, Catherine; Lafdi, Khalid; El Rhazi, Mama
Abstract: The development of highly efficient catalysts using inexpensive and earth-abundant metals is a crucial factor in a large-scale commercialization of direct methanol fuel cells (DMFCs). In this study, we explored a new catalyst based on copper nanodendrites (CuNDs) supported on carbon nanofibers/poly ( para -phenylenediamine) (CNF/P p PD) nanocomposite for methanol oxidation reaction (MOR). The catalyst support was prepared on a carbon paste electrode by electropolymerization of para -phenylenediamine monomer on a drop-cast carbon nanofibers network. Afterwards, CuNDs were electrodeposited on the nanocomposite through a potentiostatic method. The morphology and the structure of the prepared nanomaterials were characterized by transmission electron microscope, scanning electron microscope, energy dispersive X-ray, X-ray diffraction, and X-ray photoelectron spectroscope. The results suggested that a three-dimensional nanodendritic structure consisting of Cu2 O and Cu(OH)2 formed on the hybrid CNF/P p PD nanocomposite. The catalytic performance of CuNDs supported on CNF, P p PD and CNF/P p PD was evaluated for MOR under alkaline conditions. The CNF/P p PD/CuNDs exhibits a highest activity (50 mA cm −2 ) and stability toward MOR over 6 h, with respect to CNF/CuNDs (40 mA cm −2 ) and P p PD/CuNDs (36 mA cm −2 ). This inexpensive catalyst with high catalytic activity and stability is a promising anode catalyst for alkaline DMFC applications. Highlights: 3-D Cu2 O–Cu(OH)2 dendrites supported on CNF/PpPD were prepared via simple process. Good synergy in CNF/PpPD promotes electron transport and increases surface area. CNF/PpPD/CuDs exhibits outstanding catalytic activity and stability toward MOR. Efficient catalytic activity attributed to powerful synergy between CNF/PpPD and CuDs.